2022
DOI: 10.1039/d2nj00377e
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the kinetics and mechanisms of the peroxyl radical scavenging capacity of caftaric acid: the important role of the acid–base equilibrium

Abstract: Caftaric acid (CA), also known as cafeoyltartaric acid, is a molecule formed by linking caffeic acid (3,4-dihydroxy cinnamic acid) and tartaric acid through an ester moiety. This compound is found...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Moreover, it is worth noting that the overall rate constants of 5-CQA and 5-FQA are comparable to that of the reference antioxidant ascorbic acid (k = 9.97 × 10 7 M −1 s −1 ) [ 25 ] and the structurally similar system caftaric acid (k = 9.09 × 10 8 M −1 s −1 ) [ 61 ] but higher than that of Trolox (1.13 × 10 5 M −1 s −1 ) [ 63 ], BHT (2.51 × 10 5 M −1 s −1 ) [ 64 ], carnosic acid (k = 4.73 × 10 6 M −1 s −1 ) [ 65 ], and cannabidiol (k = 9.09 × 10 6 M −1 s −1 ) [ 66 ]. This indicates that 5-CQA and 5-FQA are potent antiradical agents under polar physiological conditions.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, it is worth noting that the overall rate constants of 5-CQA and 5-FQA are comparable to that of the reference antioxidant ascorbic acid (k = 9.97 × 10 7 M −1 s −1 ) [ 25 ] and the structurally similar system caftaric acid (k = 9.09 × 10 8 M −1 s −1 ) [ 61 ] but higher than that of Trolox (1.13 × 10 5 M −1 s −1 ) [ 63 ], BHT (2.51 × 10 5 M −1 s −1 ) [ 64 ], carnosic acid (k = 4.73 × 10 6 M −1 s −1 ) [ 65 ], and cannabidiol (k = 9.09 × 10 6 M −1 s −1 ) [ 66 ]. This indicates that 5-CQA and 5-FQA are potent antiradical agents under polar physiological conditions.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies indicated that the addition reaction into the α,β-unsaturated bond had no contributions to the ROO˙ radical ( i.e. , HOO˙ and CH 3 OO˙) scavenging activity, particularly in the physiological environments, 19,24,63 and RAF reaction is not supported for the π system of aromatic rings. 64,65 Thus, this reaction was omitted in our study.…”
Section: Resultsmentioning
confidence: 93%
“…In the context of antioxidant activity, deprotonated forms potentially play a key role in the mechanism underlying the interaction of PBs with free radicals. 21 Therefore, all deprotonated forms of PBs were considered in the thermodynamic and kinetic investigations of HOO • radical scavenging.…”
Section: Resultsmentioning
confidence: 99%
“…Derivatives C, D, and E with the catechol moiety react mainly via FHT from the deprotonated state, which is in agreement with previous studies on phenolic compounds containing the catechol moiety, as quercetins, 29 5-O-methylnorbergenin, 30 anthocyanidins, 31 and caftaric acid. 21 On the other hand, for F, which has two OH bonds in the para position, both SET and FHT are possible, mainly in equal ratios.…”
Section: Thermodynamic Evaluation In Physiological Mediamentioning
confidence: 99%